2016
DOI: 10.3748/wjg.v22.i10.2981
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of and risk factors for colorectal neoplasms in young adults in a screening population

Abstract: Current screening strategies for colorectal cancer may need to be amended to account for patient age, especially in young subjects with abdominal obesity, current smoking and alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 43 publications
0
68
1
Order By: Relevance
“…However, several studies have reported increasing incidence of CRC in adults under the age of 50 years; meanwhile, incidence and mortality rates in individuals over 50 are decreasing [ 7 8 9 10 11 ]. Furthermore, the prevalence of adenoma in asymptomatic healthy young-aged adults of under 50 has been reported to range from 12.5%–36%, almost equivalent to that of the elderly aged 50–60 years [ 12 13 14 15 ]. Although most adenomas stabilize and regress, removal of low-risk adenomas is reported to be effective showing 25% reduction of mortality as compared with CRC mortality rates in the general population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have reported increasing incidence of CRC in adults under the age of 50 years; meanwhile, incidence and mortality rates in individuals over 50 are decreasing [ 7 8 9 10 11 ]. Furthermore, the prevalence of adenoma in asymptomatic healthy young-aged adults of under 50 has been reported to range from 12.5%–36%, almost equivalent to that of the elderly aged 50–60 years [ 12 13 14 15 ]. Although most adenomas stabilize and regress, removal of low-risk adenomas is reported to be effective showing 25% reduction of mortality as compared with CRC mortality rates in the general population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the frequency of colorectal adenoma in young-aged adults should not be overlooked given that the majority of CRC is known to develop from colorectal adenomas through the well-known process of adenomacarcinoma sequence [ 17 ], continuous efforts have been made to clarify the risk factors for development of adenoma in young-aged adults. Several studies have proposed male sex, current smoker, alcohol consumption, obesity, and screening for colorectal adenoma as common risk factors, and those clinical factors could be indications for screening of colorectal adenoma in young-aged individuals [ 12 13 14 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and diet are associated with increased risk for CRC, and the rate of obesity among Americans has been reported to be as high as 34% (22). Physical inactivity, lack of exercise, tobacco use and consumption of alcohol are also related to increased CRC risk (23,24). These behavioral risk factors are more pervasive in populations with lower socioeconomic status in the US, thereby reflecting a relationship of demographic disparities and behavioral patterns that is associated with CRC (25,26).…”
mentioning
confidence: 99%
“…A population study is needed to further investigate the incidence, mortality and risks of colorectal cancer in this country. This is important because screening may then be implemented in higher risk groups such as those with central obesity, strong smoking history and significant alcohol consumption even at a younger age [14].…”
Section: Resultsmentioning
confidence: 99%